2014
DOI: 10.20533/licej.2040.2589.2014.0232
|View full text |Cite
|
Sign up to set email alerts
|

Quality Teacher Education in Botswana: A Crucial Requirement for Effective Teaching and Learning

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Above all, there is an urgent need for teacher preparation to incorporate the idea of ample transformation of theory into practice. One way of seeing this materialize is to ensure that teaching practice exercise is made effective through long practical experiences and serious supervision of instruction during internships [23,24]. With this in mind and all necessary measures put in place, our 21 st century student teachers can be fully prepared to face the practical reality of successful implementation of the Outcome-Based Education system with a global outlook for contemporary global citizens [25,26].…”
Section: Outcome-based Educationmentioning
confidence: 99%
“…Above all, there is an urgent need for teacher preparation to incorporate the idea of ample transformation of theory into practice. One way of seeing this materialize is to ensure that teaching practice exercise is made effective through long practical experiences and serious supervision of instruction during internships [23,24]. With this in mind and all necessary measures put in place, our 21 st century student teachers can be fully prepared to face the practical reality of successful implementation of the Outcome-Based Education system with a global outlook for contemporary global citizens [25,26].…”
Section: Outcome-based Educationmentioning
confidence: 99%
“…Most teachers prefer working alone rather than with others. It has been found that success in classrooms can be enhanced if there are teams that work together in order to boost student achievement (Feger & Arruda, 2008;Iloanya, 2014;Kohl, 2014;Neuzil, 2010;Reeves, 2006;Stewart, 2017;Waldron & McLeskey, 2010).…”
Section: Introductionmentioning
confidence: 99%